Kajian Penyusutan Luas Kawasan Hutan Sagu di Kampung Nendali Distrik Sentani Timur Kabupaten Jayapura - Semuel D. Rorrong; Terianus Luther Safkaur; Lazarus Ramandei (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The sago plant (Metroxylon sago) is native to Southeast Asia and thrives in swampy areas and riverbanks in Indonesia, with centers of distribution in Papua, Maluku, Sulawesi and Riau. In Papua, sago plays an important role in the social, economic and ecological aspects of the local community, as well as being a staple food consumed for generations. However, rapid development in Jayapura Regency, especially in Nendali Village, threatens the sustainability of the sago forest. This research uses a descriptive method to evaluate the existing condition of sago forest shrinkage through observation, interviews, and documentation. The results showed that development activities have caused the sago forest area to shrink by 114,629.76 m² between 2015 and 2020. Sago forests were converted into built-up land and open land, which amounted to 5,864.59 m² and 5,284.53 m² respectively. The SWOT analysis revealed that despite internal weaknesses, opportunities for sago forest protection exist through existing regulations. Thus, it is expected that the Jayapura District Regulation can be a reference in sustainable development and protection of sago forests for the welfare of local communities.